47 lines
2.9 KiB
C
47 lines
2.9 KiB
C
/*-*- mode:c;indent-tabs-mode:nil;c-basic-offset:2;tab-width:8;coding:utf-8 -*-│
|
||
│vi: set net ft=c ts=2 sts=2 sw=2 fenc=utf-8 :vi│
|
||
╞══════════════════════════════════════════════════════════════════════════════╡
|
||
│ Copyright 2020 Justine Alexandra Roberts Tunney │
|
||
│ │
|
||
│ This program is free software; you can redistribute it and/or modify │
|
||
│ it under the terms of the GNU General Public License as published by │
|
||
│ the Free Software Foundation; version 2 of the License. │
|
||
│ │
|
||
│ This program is distributed in the hope that it will be useful, but │
|
||
│ WITHOUT ANY WARRANTY; without even the implied warranty of │
|
||
│ MERCHANTABILITY or FITNESS FOR A PARTICULAR PURPOSE. See the GNU │
|
||
│ General Public License for more details. │
|
||
│ │
|
||
│ You should have received a copy of the GNU General Public License │
|
||
│ along with this program; if not, write to the Free Software │
|
||
│ Foundation, Inc., 51 Franklin Street, Fifth Floor, Boston, MA │
|
||
│ 02110-1301 USA │
|
||
╚─────────────────────────────────────────────────────────────────────────────*/
|
||
#include "dsp/core/core.h"
|
||
#include "libc/math.h"
|
||
#include "libc/str/str.h"
|
||
|
||
/**
|
||
* Computes 𝐀⁻¹ inverted 3×3 matrix, if it exists.
|
||
*
|
||
* @param 𝐁 is destination memory
|
||
* @param 𝐀 is input matrix, which can't overlap 𝐁
|
||
* @param 𝑑 is |𝐀| the determinant scalar or 0 if degenerate
|
||
* @return 𝐀⁻¹ stored inside 𝐁 or NaNs if 𝑑=0
|
||
* @define 𝐀⁻¹=𝐁 such that 𝐀×𝐁=𝐁×𝐀=𝐈ₙ
|
||
* @see det3()
|
||
*/
|
||
void *inv3(double B[restrict 3][3], const double A[restrict 3][3], double d) {
|
||
d = d ? 1 / d : NAN;
|
||
B[0][0] = (A[1][1] * A[2][2] - A[2][1] * A[1][2]) * d;
|
||
B[0][1] = (A[2][1] * A[0][2] - A[0][1] * A[2][2]) * d;
|
||
B[0][2] = (A[0][1] * A[1][2] - A[1][1] * A[0][2]) * d;
|
||
B[1][0] = (A[2][0] * A[1][2] - A[1][0] * A[2][2]) * d;
|
||
B[1][1] = (A[0][0] * A[2][2] - A[2][0] * A[0][2]) * d;
|
||
B[1][2] = (A[1][0] * A[0][2] - A[0][0] * A[1][2]) * d;
|
||
B[2][0] = (A[1][0] * A[2][1] - A[2][0] * A[1][1]) * d;
|
||
B[2][1] = (A[2][0] * A[0][1] - A[0][0] * A[2][1]) * d;
|
||
B[2][2] = (A[0][0] * A[1][1] - A[1][0] * A[0][1]) * d;
|
||
return B;
|
||
}
|